2021
DOI: 10.7454/ijphn.v2i1.5346
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Age, Gender, and History of Comorbid Diseases in TB Patients toward Self-Stigma TB in Surakarta

Abstract: Tuberculosis (TB) infection in Indonesia has not been completely eradicated. It is challenging for those who suffer from TB to be away from self-stigma. This study aimed to determine the relationship between age factors, gender, and a history of comorbid diseases related to self-stigma. This was a cross sectional study using a Tuberculosis Stigma Assessment questionnaire. Total 50 respondents were obtained by purposive sampling technique. Inclusion criteria are TB patients or former patients aged 18 years to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…This is the first study adapting and validating Van Rie's TB Stigma Scale to the Indonesian setting. Despite multiple studies assessing TB-stigma in Indonesia [36][37][38][39], none have previously described adaptation and validation of a TB-stigma scale prior to implementation. This new Indonesian version of the scale, consisting of an 11-item Form A (Patient Perspective) and a 10-item Form B (Community Perspective), was found to be reliable, internally consistent, and valid, and fills the knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study adapting and validating Van Rie's TB Stigma Scale to the Indonesian setting. Despite multiple studies assessing TB-stigma in Indonesia [36][37][38][39], none have previously described adaptation and validation of a TB-stigma scale prior to implementation. This new Indonesian version of the scale, consisting of an 11-item Form A (Patient Perspective) and a 10-item Form B (Community Perspective), was found to be reliable, internally consistent, and valid, and fills the knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similar results were also obtained by Widowati in 2021 in Surakarta who found that the majority of TB patients did not have comorbid chronic diseases. 26 However, Salihi in 2020, who conducted a study on 1160 TB patients of productive age, obtained different results, namely the majority of TB patients had comorbid chronic diseases. 27 According to Padrão, this can be attributed to a reverse causality bias, namely by considering that the individual adopts a healthy lifestyle because the individual has a chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Help-seeking behavior may be hampered because of hiya (shame) for having an illness, which have implications on their psychological and physical well-being. In Indonesia, there is a similar concept of malu (shame) related to perceived stigma, for example, among people with tuberculosis who are ashamed of their illness and, consequently, it affects their psychological well-being (Widowati & Mulyani, 2021).…”
Section: Covid-19-related Stigma and Quality Of Lifementioning
confidence: 99%